Larger Subcortical Gray Matter Structures and Smaller Corpora Callosa at Age 5 Years in HIV Infected Children on Early ART - Randall, Steven R.; Warton, Christopher M. R.; Holmes, Martha J.; Cotton, Mark F.; Laughton, Barbara; van der Kouwe, Andre J. W.; Meintjes, Ernesta M. (Frontiers in Neuroanatomy, 2017)
Sub-Saharan Africa is home to 90% of HIV infected (HIV+) children. Since the advent of antiretroviral therapy (ART), HIV/AIDS has transitioned to a chronic condition where central nervous system (CNS) damage may be ongoing. Although most guidelines recommend early ART to reduce CNS viral reservoirs, the brain may be more vulnerable to potential neurotoxic effects of ART during the rapid development phase in the first years of life. Here we investigate differences in subcortical volumes between 5-year-old HIV+ children who received early ART (before age 18 months) and uninfected children using manual tracing of Magnetic Resonance Images. Participants included 61 Xhosa children (43 HIV+/18 uninfected, mean age = 5.4±0.3 yrs, 25 male) from the children with HIV early antiretroviral (CHER) trial; 27 children initiated ART before 12 weeks of age (ART-Before12Wks) and 16 after 12 weeks (ART-After12Wks). Structural images were acquired on a 3T Allegra MRI in Cape Town and manually traced using MultiTracer. Volumetric group differences (HIV+ vs uninfected; ART-Before12Wks vs ART-After12Wks) were examined for the caudate, nucleus accumbens (NA), putamen (Pu), globus pallidus (GP) and corpus callosum (CC), as well as associations within infected children of structure volumes with age at ART initiation and CD4/CD8 as a proxy for immune health. HIV+ children had significantly larger NA and Pu volumes bilaterally and left GP volumes than controls, whilst CC was smaller. Bilateral Pu was larger in both treatment groups compared to controls, while left GP and bilateral NA were enlarged only in ART-After12Wks children. CC was smaller in both treatment groups compared to controls, and smaller in ART-After12Wks compared to ART-Before12Wks. Within infected children, delayed ART initiation was associated with larger Pu volumes, effects that remained significant when controlling for sex and duration of treatment interruption (left β = 0.447, p=0.005; right β = 0.325, p=0.051), and lower CD4/CD8 with larger caudates controlling for sex (left β = -0.471, p=0.002; right β = -0.440, p=0.003). Volumetric differences were greater in children who initiated ART after 12 weeks. Results suggest damage is ongoing despite early ART and viral load suppression; however, earlier treatment is neuroprotective.